Dairy buffalo production system under semi-intensive management in the coastal area of Bangladesh - Rahman, SMR; Islam, MN; Rashid, MH; Siddiki, MSR; Islam, MA (SAARC Journal of Agriculture, 2019)
This study was conducted to evaluate the present status of production system of dairy buffalo under semi-intensive management in coastal area of Bangladesh. The data were collected during farm visit and recorded in prepared questionnaire and check list. The findings of the study revealed that very minimum housing facilities were provided to the buffaloes. Both the grazing and confinement time were found similar (around 6 hrs in a day) and they spent almost 3 hrs in a day for wallowing. The majority of the lactating buffaloes were not being adequately fed. Farmers usually supplied local grass (4.98±2.89 kg DM/day) and rice straw (10.90 ±2.85 kg DM/day) with one or two concentrate feed separately as supplement (1.51±0.80 kg DM/day). The daily average DCP and TDN supply were 0.365 and 6.417 kg/d respectively which were undersupplied as compared to standard requirement. The productive and reproductive performance of indigenous dairy buffalo was not similar to high producing dairy buffaloes. The average lactation yields (litre/lactation) were found as 469.52±163.71. The EC value (2.73±3.53) of milk indicated as healthy milk production. Milk consumption pattern (8%) was not satisfactory. Milk market was volatile. Natural breeding (95.7%) was more prominent practice than artificial insemination (AI) (4.3%). The most of the buffalo cows showed heat from early night to early morning (22.2-54.2%). Technology adaptation for buffalo rearing was very much poor. Technology adaptation index for the use of concentrate feed, artificial insemination, de-worming and vitamin-mineral premix were 16.34, 13.46, 23.07 and 6.25 respectively. It therefore be concluded that technological transformation could be boost up to national milk production by developing of the management practise of dairy buffalo under semiintensive system in Bangladesh. SAARC J. Agri., 16(2): 43-59 (2018)